Estratégias e modelos sucessórios em propriedades rurais do município de Cruz Alta/RS - Moreira, Sandro da Luz (2018)
This dissertation has as central theme the social reproduction of rural properties in the municipality of Cruz Alta, Rio Grande do Sul, analyzing the generational succession in rural properties characterized by agribusiness. It is an innovative study, advancing on the theme of social reproduction in rural areas, in so far as they propose to make use of the livelihoods approach, whose main author Frank Ellis (2000), together with the approach of the succession models of Ruth Gasson and Andrew Errington (1993). The proposal in this work is centered in understanding the succession processes in rural properties of the municipality of Cruz Alta. More specifically, it was analyzed the strategies used by parents to encourage the permanence of the children and the way these motivations or strategies are fostered by parents within the properties. From this analysis of the strategies, the types or succession models found were presented. The models are built from the way parents infer autonomy over work, management and income of the successors, following the model proposed by Gasson and Errington (1993). The methodology used was a qualitative research, the instrument of data collection was semi-structured interviews, and the procedure used for data analysis was content analysis. The choice of producers was based on the indication in the Rural Unions of the Municipality and the criteria used for selection followed those proposed in the work of Spanevello (2008): Have at least one child, regardless of gender; farmers aged 50 years old or more. This age cut is justified by the fact that the research focuses on cases of a defined or directed situation of succession. There were 31 interviews, covering different properties in terms of size, productive systems and places of residence of managers. The results showed that the greater the portfolio of capital and the quantity of assets available in the producers' livelihoods, the greater the ease of maintaining a successor in the rural property. Therefore, these assets and capital are used as strategies to mobilize generational succession on rural properties. Six strategies types were found: Motivational strategy linked to occupation; Autonomy strategies; New investment strategy; Study supply strategy; Strategy of urban occupation and Strategy of donation of goods. From the strategies of mobilization of Ellis capitals, the succession models found in the rural properties of Cruz Alta / RS were found. It was found seven distinct succession models, where the main variables considered were: the place of residence - rural property or city; business management (bureaucratic, productive management) - partial or total; and income management - income autonomy or dependent on parents.